2020
DOI: 10.3390/biology9090284
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Early Menopause on Adiposity, Fatty Acids Profile and Insulin Sensitivity of a Swine Model of Female Obesity

Abstract: Menopause strongly increases incidence and consequences of obesity and non-communicable diseases in women, with recent research suggesting a very early onset of changes in lipid accumulation, dyslipidemia, and insulin resistance. However, there is a lack of adequate preclinical models for its study. The present trial evaluated the usefulness of an alternative method to surgical ovariectomy, the administration of two doses of a GnRH analogue-protein conjugate (Vacsincel®), for inducing ovarian inactivity in sow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…According to the World Health Organization, overweight and obesity are a major risk factor for heart disease, including high blood pressure, which is the number one cause of death [ 31 ]. In our study, the odds of hypertension were two times higher among obese participants compared to those with normal body mass index; however, the chances of hypertension were reduced by 73% among underweight participants.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, overweight and obesity are a major risk factor for heart disease, including high blood pressure, which is the number one cause of death [ 31 ]. In our study, the odds of hypertension were two times higher among obese participants compared to those with normal body mass index; however, the chances of hypertension were reduced by 73% among underweight participants.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is well known that female after menopause is an one of the risk factor of type 2 diabetes mellitus, hyperlipidemia, and visceral fat obesity due to imbalanced sex hormone metabolism. 16,[28][29][30] Since all of these factors might be associated with the development of conventional fatty liver, 31 several reports presumed that imbalance of sex hormone metabolism might be strongly associated with the development of NAFLD after TP. 13,16 In the present study, however, we could not assess the population of menopaused women, and therefore further study is needed to prove this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al 27 showed that in patients aged 50 years or older, the severity of hepatic steatosis was worse among women than among men, possibly because the protective effect against fat deposition into hepatocytes in women is eliminated after menopause. Furthermore, it is well known that female after menopause is an one of the risk factor of type 2 diabetes mellitus, hyperlipidemia, and visceral fat obesity due to imbalanced sex hormone metabolism 16,28‐30 . Since all of these factors might be associated with the development of conventional fatty liver, 31 several reports presumed that imbalance of sex hormone metabolism might be strongly associated with the development of NAFLD after TP 13,16 .…”
Section: Discussionmentioning
confidence: 99%